The Role of Ilha Study Program Students in Spreading the Values ​​of Religious Moderation on Social Media - Mifta, Miftahul Janah; Ahmad Arifi; Indal Abror (Jurnal Studi Agama, 2024)
The main aim of this research is to understand and analyze in depth how students from the Al-Qur'an and Tafsir Science Study Program (Ilha) play an active role in spreading the values ​​of religious moderation through social media. This research problem focuses on the important role of the younger generation, especially Ilha Study Program students, in facing the challenges of radicalism and intolerance which are often spread through social media. This research tries to answer the question of how Ilha Study Program students can become agents of change in spreading the values ​​of religious moderation in the digital space. Qualitative research method with field research type, conducting in-depth interviews with Ilha Study Program students to dig deeper into the i, challenges, strategies, as well as supporting and inhibiting factors they face in spreading the values ​​of religious moderation.    The results of this research can provide a comprehensive picture of the role of Ilha Study Program students in spreading the values ​​of religious moderation on social media. identify strategies used by Ilha Study Program students, such as creating creative content, online discussions, social media campaigns, and collaboration with other parties. The challenges faced are lack of good understanding or just following trends, and manipulation of information or hoax news. The supporting and inhibiting factors for Ilha Study Program students in spreading the values ​​of religious moderation are the influence of peers, being quick and interactive, while the inhibiting factors are a lack of increasing understanding or reducing negative content on social media